Employee Performance Optimization: Improving Work Discipline and Effective Communication - Derni DERNI; Andi Indriani IBRAHIM; Risnawati PALU (PT Keberlanjutan Strategis Indonesia, 2025)
The purpose of this study is to analyze the optimization of Morowali Airport employee performance by testing and analyzing the partial and simultaneous influence of work discipline, work motivation and effective communication. The type of research used is a quantitative approach. The population of this study was all Morowali Airport employees, totaling 63 people. By using the census method, the entire population in this study was used as a sample. This study analyzed the data using multiple linear regression. The results of the study indicate that there is a positive and significant influence of work discipline, work motivation and effective communication on the performance of Morowali Airport employees, both partially and simultaneously. It shows that employee performance achievement is largely determined by work discipline and effective communication built by Morowali Airport employees. In addition, the work discipline variable is the variable that has the greatest influence on employee performance. Thus, this study recommends that Morowali Airport employees improve their work discipline in order to improve the quality and quantity of their work results so that they can achieve high performance.